Combining sequence-specific probes and DNA binding dyes in real-time PCR for specific nucleic acid quantification and melting curve analysis. (March 2006) - Lind, Kristina; Ståhlberg, Anders; Zoric, Neven; Kubista, Mikael
Currently, in real-time PCR, one often has to choose between using a sequence-specific probe and a nonspecific double-stranded DNA (dsDNA) binding dye for the detection of amplified DNA products. The sequence-specific probe has the advantage that it only detects the targeted product, while the nonspecific dye has the advantage that melting curve analysis can be performed after completed amplification, which reveals what kind of products have been formed. Here we present a new strategy based on combining a sequence-specific probe and a nonspecific dye, BOXTO, in the same reaction, to take the advantage of both chemistries. We show that BOXTO can be used together with both TaqMan® probes and locked nucleic acid (LNA) probes without interfering with the PCR. The probe signal reflect formation of target product, while melting curve analysis of the BOXTO signal reveals primer-dimer formation and the presence of any other anomalous products.